Morphometric analysis of supraoptic neurons of the rat hypothalamic nuclei under conditions of prolonged illumination - Bulyk, R.; Smetaniuk, O.; Bulyk, T.; Kryvchanska, M. (Journal of Education, Health and Sport, 2021)
The article reviews the results of studies of the morphofunctional state of neurons of the supraoptic nuclei of the rat hypothalamus under conditions of different duration of light regime. Under standard light regime in rats, a diurnal rhythm of morphofunctional activity of supraoptic nucleus neurons with maximum activity during daytime (before 2 p.m.) is recorded. In animals subjected to prolonged light exposure, more pronounced changes in the morphofunctional state of the supraoptic neurons of the hypothalamus at 2 a.m. than at 2 p.m. were established. Thus, the neuronal nucleus area was 94.08 ± 9.55 μm2 and was significantly greater than that in intact animals. The nucleo-cytoplasmic ratio of supraoptic hypothalamic neuron at 2 a.m. was lower than that in intact animals due to a decrease in specific nucleus volume. In comparison with the day period (2 p.m.), before 2 a.m. there was revealed a decrease of the neuron body area of supraoptic nuclei of hypothalamus due to possible decrease of the area of nucleus and nucleolus of cells. This was the reason for the increase in the nucleo-cytoplasmic ratio in the neurons under observation at night, which was 2.51 ± 0.023 units. Constant light regime did not cause inversion of the rhythm of morphofunctional activity of the neurons under study, the maximum values, as in intact animals, occurred in the daytime observation period.